The influence of emotional intelegence, self-efficacy, and altruism on teacher’s competence in inclusion elementary school - Devalia Septiana (Jurnal Prima Edukasia, 2018)
This study aimed to: (1) describe emotional intelligence, self-efficacy, altruism, and teachers’ performance who teach in inclusion elementary schools of Karanganyar District, and (2) determine the effect of emotional intelligence, self-efficacy, and altruism on teachers competence who teach in inclusion elementary school of Karanganyar District. The research was quantitative research using the ex-post facto method. The results of the study show that: (1) teacher’s emotional intelligence is at the medium category, while self-efficacy, altruism, and teachers competence who teach in inclusion elementary school of Karanganyar District are in high category; (2) there is a significant relationship between emotional intelligence with the teacher’s competence, with a value of r = 0.560 (r 0,244 ),  there is a significant relationship between self-efficacy with teacher’s competence with a value of r =0.535 ( r 0.244), there is a significant relationship between altruism with the teacher’s competence, with a value of r = 0.711 (r 0.244 ) and there is a significant relationship between emotional intelligence, self-efficacy, and altruism with the teacher’s competence, with a value of F = 39.742 (F 2.76). Therefore, it concluded that higher emotional intelligence, and altruism the higher the teacher’s competence.